Activity-Based Costing System Dalam Penetapan Harga Pokok Produksi Serta Pengaruhnya Terhadap Kinerja Perusahaan (Studi Kasus Industri Kain Tenun Ikat Medali Mas Di Kota Kediri) - Kusumaningtyas, Dian; Izzatul, Rilla (UNIVERSITAS NUSANTARA PGRI KEDIRI, 2017)
Kediri has Tenun Ikat centers so that people have opportunities to improve their standard of living through weaving industry . In the embodiment , the necessary foundation of the formation of a strong organization in the industry SMEs, especially craftsman weaving Medal Mas Kediri on managerial human resources, marketing , production and managerial finance in preparing business continuity in the long-term direction . Method cost of product is defined as a way to take into account the elements of cost into the cost of production . In the process of calculating all elements of cost into the cost of production of the many businesses went a different way. The concept of Activity Based Costing or ABC method is an alternative to overhead cost. Based on the background that has been described so obtained formulation of the problem